A Rudimentary Study of CSR Application in Islamic Financial Institutions in Malaysia - Ismail, Sara Iriana (2013)
Recently, we see the concept of CSR evolving from ethical needs of the capitalist culture to operational creativity as companies have been adopting new ways to enhance and enable different initiatives to address stakeholder concerns. Driven by the market expectation and value creation, companies are widely recognised as a major driving force behind industry trends and Islamic financing is not an exception. CSR is currently emerging as a popular vehicle to promote competitive advantage or acts as a differentiator in projecting company image to takeholders. However, for Islamic financial institutions, CSR are meant to be a mandatory responsibility anyway. This research analyses a sample of four Islamic financial institutions on current CSR practices while identifying gaps or improvements that has been made and proven effective.